Inspiratory muscle resistance combined with strength training: effects on aerobic capacity in artistic swimmers - Yuncai Fan; Yucheng Duan; Zhiqing Gao; Yong Liu (Frontiers in Sports and Active Living)
ObjectiveThis study aimed to investigate the effects of combining inspiratory muscle resistance with strength training on lung function and aerobic capacity in artistic swimmers.MethodsThis research constitutes a placebo-controlled randomized trial, involving a five-week walking program conducted twice a week. Fourteen female artistic swimmers were randomly assigned to either the experimental group (TG group, n = 7) or the control group (CG group, n = 7). Both groups underwent the same strength training program. The TG group performed inspiratory muscle strengthening at 50% of maximum inspiratory pressure (MIP) during strength training, whereas the CG group engaged in strength training with 15% MIP inspiratory muscle training twice a week. Pre- and post-intervention assessments included an incremental stress test, pulmonary function test, inspiratory muscle strength test, and a specialized performance test.ResultsFollowing the 5-week intervention, within-group comparisons revealed that the inspiratory muscle strength index, vital capacity, and forced vital capacity significantly increased in both the CG and TG groups (P < 0.01). The TG group exhibited a significant increase in minute ventilation (P < 0.05), while the CG group showed a significant increase in tidal volume (P < 0.05). Additionally, the TG group demonstrated a significant improvement in running speed at the ventilation threshold and maximum oxygen uptake (P < 0.05), along with a significant increase in tidal volume (P < 0.01). Both the CG and TG groups showed significant increases in the scores for the 50-meter diving and 25-meter torpedo (P < 0.05). Between-group comparisons showed that the TG group experienced significant improvements in the inspiratory muscle strength index, minute ventilation, running speed corresponding to maximum oxygen uptake, and 25-meter torpedo performance (P < 0.05).ConclusionThe findings suggest that a 5-week program combining inspiratory muscle resistance with strength training can effectively enhance the aerobic exercise capacity of artistic swimmers. Moreover, high-intensity inspiratory muscle resistance combined with strength training can improve the muscle's ability to utilize oxygen during exercise. Trial RegistrationBeijing Research Institute of Sports Science (TKSLL202201); China Clinical Trial Registry, ChiCTR2300072833, 26/06/2023.